2020
DOI: 10.3389/fpsyg.2020.581025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Board Game Designed to Promote Young Children’s Delay of Gratification

Abstract: Objective Delay of gratification, or the extent to which one can resist the temptation of an immediate reward and wait for a larger reward later, is a self-regulatory skill that predicts positive outcomes. The aim of this research was to conduct initial tests of the effects of a board game designed to increase children’s delay of gratification via two experimental studies. Methods Preschool children were randomized to play the study game or a control game. In Study 1, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Each of the 19 studies [1,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] included for final analysis were reviewed to ensure the data analyses performed were specifically and appropriately reporting intervention effects (i.e., growth in intervention group compared to a control condition). Two studies [64,65] were excluded from the analysis because intervention effects were not reported and could not be computed from the published data.…”
Section: Critical Appraisal Of Individual Sources Of Evidencementioning
confidence: 99%
“…Each of the 19 studies [1,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] included for final analysis were reviewed to ensure the data analyses performed were specifically and appropriately reporting intervention effects (i.e., growth in intervention group compared to a control condition). Two studies [64,65] were excluded from the analysis because intervention effects were not reported and could not be computed from the published data.…”
Section: Critical Appraisal Of Individual Sources Of Evidencementioning
confidence: 99%